Analisis Kesiapan Penerapan Kebijakan Badan Layanan Umum Daerah (BLUD) Puskesmas di Kabupaten Kulon Progo (Studi Kasus di Puskesmas Wates dan Puskesmas Girimulyo II Kabupaten Kulon Progo) - Albertus Sunuwata Triprasetya; Laksono Trisnantoro; Ni Luh Putu Eka (Jurnal Kebijakan Kesehatan Indonesia, 2014)
Background: Some community health centers in Kulon Progo Regency had managed to meet their own operational needs without depending upon the subsidiary from the local govern- ment. However, bureaucratic problems often led to difficulties in realizing the funds. Long and exhausting bureaucratic pro- cedures and lack of flexibility in the fund use had delayed the public health services at the health centers. Implementation of the Local Public Service Agency (BLUD) at the Health Centers was a proposed solution for the problem. The Health Services that served as BLUD could use the budget/local income to support operation of the health facilities (i.e. flexibility in the fund use) without prior deposit to the local government ac- count. The purpose is to slim down the bureaucratic chains, thus allowing the Health Centers to improve their performance. This way, they could be more productive, effective, efficient, and ready to exercise the Social Security Agency (BPJS) in 2014. Of course, implementation of the policy requires active roles of the stakeholders and supporting conditions at the Health Centers. The study was conducted based on the facts, that all of the Health Centers in Kulon Progo Regency would implement the Local Public Service Agency (BLUD), as speci- fied by the Ministry of Domestic Affairs’ Regulation (Permendagri) No. 61/2007 on the Technical Guides for Finan- cial Management of BLUD. Objectives: To analyze to what extent the Health Centers were ready for the implementation of the Local Public Service Agency (BLUD) in Kulon Progo Regency. Methods: The research was a qualitative approach, using descriptive analytical method and case study design to as- sess the facts on readiness of the Health Centers to apply the BLUD policy. The analysis involved technical and administra- tive requirements of the Health Centers, analysis on the stake- holder roles, and analysis on the real situations at Wates and Girimulyo II Health Centers in Kulon Progo Regency. The re- search used purposive sampling technique, while the data were collected by means of in-depth interviews, observation, and library study. Results: Wates and Girimulyo II Health Centers in Kulon Progo were not fully prepared with technical requirements for the implementation of Health Center BLUD Policy: The increasing rate of earning during the last three years is not complemented by the result of evaluationservice performance thatwas not optimal.Health Centers in Kulon Progo were ready with admin- istrative requirements for the implementation of Health Center BLUD Policy.Stakeholders in Kulon Progo Regency also sup- ported the policy implementation, as evident from the analysis that the stakeholders played important roles and interests but were not ready with supporting regulation for Health Center BLUD Policy. However, the study found that the real conditions at the Health Centers were not ready to support BLUD, as evident from lack of commitment from the Health Centers, inad- equate financial management system, and inadequate human resources for financial management at the Health Centers. Conclusion: Overall, The Health Center in Kulon Progo has not been fully ready to implement BLUD, it must be supported by regulation and adequate resources. Latar Belakang: Beberapa Puskesmas di Kabupaten Kulon Progo sudah bisa mencukupi kebutuhan operasionalnya tanpa tergantung subsidi dari Pemda, namun untuk pencairan dananya sering kali tidak tepat waktu karena masih terkendala alur birokrasi. Alur birokrasi yang terlalu panjang dan tidak adanya fleksibilitas dalam penggunaan dana menghambat kelancaran pelayanan pada puskesmas. Penerapan kebijakan BLUD Pus- kesmas merupakan solusi untuk mengatasi permasalahan tersebut. Puskesmas BLUD, dana/pendapatan puskesmas bisa digunakan langsung untuk operasional (fleksibilitas penggunaan dana) tanpa disetor ke pemda, sehingga bisa memotong rantai birokrasi pemda dan dengan demikian puskesmas dapat meningkatkan kinerja pelayanannya secara produktif, efektif, dan efisien dan siap menyongsong diberlakukannya program BPJS Tahun 2014. Dibutuhkan peran stakeholder dan suasana di puskesmas yang mendukung kesiapan penerapan kebijakan ini. Penelitian ini dilakukan berdasarkan kenyataan, seluruh Puskesmas di Kabupaten Kulon Progo akan menerapkan Badan Layanan Umum Daerah (BLUD) sesuai dengan Peraturan Men- teri Dalam Negeri (Permendagri) No. 61 Tahun 2007 tentang Pedoman Teknis Pola Pengelolaan Keuangan Badan Layanan Umum Daerah. Tujuan: Menganalisis dan mengetahui sejauh mana kesiapan penerapan kebijakanBLUD Puskesmasdi Kabupaten Kulon Progo. Metode:Dalam penelitian ini, peneliti menggunakan jenis penelitian kualitatif dengan metode analisis deskriptif dengan rancangan studi kasus untuk menggambarkan keadaaan serta menggali secara luas kesiapan penerapan kebijakan BLUD Puskesmas, dengan menganalisis kesiapan persyaratan teknis dan administratif Puskesmas, analisis peran stakeholder, meng- analisis suasana yang ada di Puskesmas Wates dan Girimulyo II dalam kesiapan penerapan kebijakan BLUD Puskesmas diKabupaten Kulon Progo. Pengambilan sampel pada penelitian ini dilakukan secara purposive sampling. Metode pengumpulan data diperoleh dengan wawancara mendalam (indepth inter- view), observasi dan pemanfaatan dokumen. Hasil:Puskesmas Wates dan Girimulyo II di Kabupaten Kulon Progo belum siap sepenuhnya dengan persyaratan teknis, hal ini ditunjukkan dengan tingkat pendapatan puskesmas yang meningkat dalam tiga tahun terakhir tetapi hasil evaluasi kinerja pelayanan puskesmas belum optimal. Puskesmas telah siap dengan persyaratan administratif ditunjukkan dengan keleng- kapan dokumen BLUD Puskesmas. Stakeholder di Kabupaten Kulon Progo mendukung dalam penerapan kebijakan BLUD Puskesmas, ditunjukkan dari hasil analisis yang menunjukkan tingkat pengaruh dan kepentingan stakeholder yang cukup tinggi tetapi belum sepenuhnya siap dengan regulasi BLUD Puskesmas. Suasana yang terlihat pada Puskesmas kurang mendukung, dilihat dari komitmen puskesmas yang masih ku- rang, sistem pengelolaan keuangan puskesmas yang belum mendukung dan bendahara puskesmas yang belum terlatih pengelolaan keuangan BLUD. Kesimpulan: Secara keseluruhan kesiapan penerapan kebijakan BLUD Puskesmas di Kabupaten Kulon Progo belum sepenuhnya dilaksanakan, perlu segera ditindaklanjuti dengan regulasi yang mendukung dan kecukupan sumber daya.